Treg engage lymphotoxin beta receptor for afferent lymphatic transendothelial migration - C. Colin Brinkman; Daiki Iwami; Molly K. Hritzo; Yanbao Xiong; Sarwat Ahmad; Thomas Simon; Keli L. Hippen; Bruce R. Blazar; Jonathan S. Bromberg (Nature Communications, 2016)
Lymphotoxin regulates lymphoid organ architecture and adhesion molecules involved in lymphocyte trafficking. Here the authors show that lymphotoxin produced by regulatory T cells promotes their migration to the draining lymph nodes by engaging its cognate receptor on lymphatic endothelial cells.